Daniel's gift - Helldorfer, M. C. (New York : Aladdin Books, 1987)
Three Shepherd boy's guard their sheep in the hills near Bethlehem the night Jesus is born.
Keywords: Jesus Christ - Juvenile fiction; Jesus Christ -- Nativity -- Fiction